Deep-level spectroscopy in metal–insulator–semiconductor structures. (12th January 2017) - Kurtz, A; Muñoz, E; Chauveau, J M; Hierro, A
Abstract: In this study we present a method for measuring bulk traps using deep-level spectroscopy techniques in metal–insulator–semiconductor (MIS) structures. We will focus on deep-level transient spectroscopy (DLTS), although this can be extended to deep-level optical spectroscopy (DLOS) and similar techniques. These methods require the modulation of a depletion region either from a Schottky junction or from a highly asymmetric p–n junction, junctions that may not be realizable in many current material systems. This is the case of wide-bandgap semiconductor families that present a doping asymmetry or have a high residual carrier concentration or surface carrier accumulation, such as InGaN or ZnO. By adding a thin insulating layer and forming an MIS structure this problem can be circumvented and DLTS/DLOS can be performed under certain conditions. A model for the measurement of bulk traps in MIS structures is thus presented, focusing on the similarities with standard DLTS, maintaining when possible links to existing knowledge on DLTS and related techniques. The model will be presented from an equivalent circuit point of view. The effect of the insulating layer on DLTS is evaluated by a combination of simulations and experiments, developing methods for the measurement of these type of devices. As a validation, highly doped ZnO:Ga MIS devices have been successfully characterized and compared with a reference undoped sample using the methods described in this work, obtaining the same intrinsic levels previously reported in the literature but in material doped as high as 1 × 10 18 cm −3 .